Song pitch indicates body size and correlates with males' response to playback in a songbird. (May 2015) - Linhart, Pavel; Fuchs, Roman
Abstract : The inverse relationship between body size and vocalization pitch has been described in a number of species. Nevertheless, the existence of size–pitch allometry within any songbird species is surprising due to the small size variation between males, the determinate growth and exceptional vocal prowess of the taxon. The phenomenon has been documented in only a few songbird species so far and the consequences of allometry remain unclear in this taxonomic group. In this study, we provide evidence that song spectral features are related to one of the body size components (tarsus length) even in a very small songbird species: the willow warbler, Phylloscopus trochilus . Moreover, the response of territorial males was affected by the pitch asymmetry between the subject and the playback stimulus: the lower-pitched the subject's song in respect to the stimulus the bolder was its response. Our results suggest that willow warbler males may use song pitch to assess the body size of their rivals (i.e. their fighting ability) in male–male competition for resources. Highlights: Size-pitch allometry is little studied in songbirds. We revealed size-pitch allometry in songs of a small songbird: the willow warbler. Bigger males (tarsus as proxy for body size) had lower songs. Males' responses covaried with pitch asymmetry between subject and stimulus. Males kept further from and were more active with stimuli representing bigger threat.